IMPLEMENTATION OF FOOD SECURITY PROGRAMS IN CORRECTIONAL INSTITUTIONS IN THE BANTEN REGION - Ananta Marchelino Syahputra; Irvan Sebastian Iskandar (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study analyzes the implementation of the Food Security Program in eight correctional institutions in the Banten region as part of inmate rehabilitation efforts. The research uses a qualitative approach, with data collected through observation and in-depth interviews involving correctional officers and inmates. The findings show that the program provides tangible benefits, particularly in reducing food procurement costs (BAMA) and improving inmates’ skills through agricultural and productive activities. However, its implementation has not yet been optimal. Several obstacles were identified, including the absence of clear national technical regulations, limited land availability, inadequate infrastructure, and a shortage of skilled personnel. Some institutions, such as the open prison model, have shown more progress by approaching the minimum contribution target, while others are still in the early stages of development. The analysis, based on the implementation theory of Grindle and the empowerment concept of Julian Rappaport, highlights the importance of strong institutional support, capacity building, and the development of an integrated evaluation system. These elements are essential to ensure the sustainability and effectiveness of the Food Security Program in correctional institutions. Keywords: Food Security; Correctional Institutions; Policy Implementation; Prisoner Empowerment